The Relationship between Nutritional Status of Women before Pregnancy with the Incidence of Chronic Enerhy Lack in Pregnant Women - Anggun Novita Sari; Arika Indah Setyarini; Ririn Indriani; Ira Titisari (GLOBAL HEALTH SCIENCE GROUP, 2023)
If a pregnant woman goes without enough nutrition (namely, carbs and fats), she may suffer from KEK.Objective: The purpose of this research was to examine the possible association between pre-pregnancy maternal nutritional health and the incidence of chronic energy deficiency (KEK). Method: A total of 38 participants were surveyed and studied utilizing a retrospective cohort design for this quantitative correlation study. The Sperman rank test is used for analysis of both bivariate and univariate data.Results: Study findings indicate a possible association between pregnant women's nutritional status and the prevalence of KEK in the Kademangan status Center's service area (p = 0.026, p 0.05).Conclusions: The findings of this study suggest that pregnant women should think about their nutritional condition before becoming pregnant in order to protect the health of themselves and their unborn children.